Implementasi Multi-Objective Optimization on the basis of Ratio Analysis (MOORA) Sebagai Pendukung Keputusan Pembelian Telepon Seluler - Irfan, Irfan Dwi Yulianto; Wibisono, Setyawan (Universitas Sari Mutiara Indonesia Medan, 2023)
A cell phone is a device or communication tool that can be used anytime and anywhere because it can be carried anywhere. There are various types and types of cell phones, so that between cell phones have different specifications. This often makes it difficult for consumers to choose a cell phone. Decision Support System is a system that can help someone in making a decision. One of the SPK methods that can help in choosing a cell phone is the MOORA method. One of the advantages of this method is high flexibility and a good level of selectivity. This study aims to implement the MOORA method as a support for purchasing decisions on cellular phones. In this study, five criteria were used, namely RAM, Camera, Storage, Price and Thickness. Where the criteria for RAM, Camera and Storage are the benefit types, while Price and Thickness are the cost types. Based on the results of the study using the MOORA method, the highest score was 0.0516 as the best alternative cell phone.